XMM-Newton X-ray observations of the Carina nebula - Albacete Colombo, Juan Facundo (2003)
We use new XMM-Newton observations to perform a detailed X-ray analysis of the Carina nebula region in the 0.3-12 keV energy range. Our source detection yields 80 discrete X-ray sources, from which about 20 per cent seem not to have optical counterparts. To get an idea of the energy spectrum of these sources, we construct an X-ray.colour-colour diagram using the energy bands 0.3-2, 2-4.5 and 4.5-12 keV. We analyse the spectra of the most intense X-ray sources associated with early-type stars, including the luminous blue variable η Carina and WR25. We show that the X-ray emission from these sources is well fitted by multitemperature model spectra. We detect surprisingly intense X-ray emission at energies above 4 keV for some of the observed early-type stars, especially from CPD-59 2629 (Tr16-22) which presents particularly hard X-ray emission. We detect intense soft X-ray emission, below <2 keV, in HDE 303311, which presents an X-ray excess of about 100 times higher than has been observed in other 05V stars. We use these data to construct the L x/Lbol relation for the 0.3-12 and 3.0-12 keV energy ranges, for all the observed O-type stars, plus η Carina and WR25. Most of the bright stars seem to agree with low metallicity spectral models. The L x/Lbol ratio for O-type stars in the 0.3-12 keV range is well fitted by a constant ≈6.04.87.5 × 10 -7, in fair agreement with the canonical expression L x/Lbol ∼ 2 × 10-7 formerly estimated for the 0.3-2.4 keV energy band. In contrast, the Lx/Lbol relation for the 3.0-12 keV range presents a strong deviation from the canonical relation, with a high dispersion of about four orders of magnitude. We also detect intrinsic X-ray time variability in seven sources, over the time-scale of about 50 h covered by the observations. This includes an X-ray flare of about 2-h duration detected in DETWC Tr16 J104429.2-594143, a source probably not physically associated with the Carina nebula. We discuss the different underlying physical mechanisms that can be responsible for the X-ray emission from early-type stars.